Overview of knowledge monitoring online systems - V. H. Hrytsenko; L. I. Hladka (Academy of Cognitive and Natural Sciences, 2014)
The aim of this study is analysis of the online services of knowledge testing. Objectives of the study is to determine the types and categories of the most popular online services of testing, selection of features. The object of research is the process of computer-based testing. The subject of research is the use of online services for computer testing. The paper stressed the relevance of the use of computer-based testing in the learning process. Indicated that online testing services for organizations with features such as mobility, cross-platform and the opportunity instant use. The review of online services designed to create tasks and test control of knowledge. Highlighted two categories of services online knowledge testing.